2019
DOI: 10.1029/2018jg004896
|View full text |Cite
|
Sign up to set email alerts
|

Global Meta‐Analysis on the Relationship Between Mercury and Dissolved Organic Carbon in Freshwater Environments

Abstract: In freshwater ecosystems, several studies have shown a strong linear relationship between total mercury (THg) or methylmercury (MeHg) and dissolved organic carbon (DOC) concentrations. Variations in this linear relationship have been reported, but the magnitude and causes of this variation are not well known. The objective of this study was to conduct a meta‐analysis to quantify and understand the global variation of this mercury (Hg)–DOC association. This meta‐analysis included 54 studies in lentic and lotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 116 publications
(290 reference statements)
8
50
0
Order By: Relevance
“…The reported ratios between FTHg and DOC (0.144-0.167 ng mg −1 ) and between FMeHg and DOC (0.051-0.053 ng mg −1 ) in this study of the Waccamaw River are similar to other lake and river studies in the North America that were recently compiled by Lavoie et al (2019) and for which the ratio between FTHg and DOC was found to be 0.30 AE 0.19 ng mg −1 (compiled from 31 studies on 1973 samples) and the ratio between FMeHg and DOC was found to be 0.045 AE 0.06 ng mg −1 (compiled from 20 studies on 1068 samples). These relationships suggest similar binding capacities of DOC to THg and MeHg in watersheds across a large geographic gradient.…”
Section: Transport and Sources Of Mercury In Riverssupporting
confidence: 89%
See 1 more Smart Citation
“…The reported ratios between FTHg and DOC (0.144-0.167 ng mg −1 ) and between FMeHg and DOC (0.051-0.053 ng mg −1 ) in this study of the Waccamaw River are similar to other lake and river studies in the North America that were recently compiled by Lavoie et al (2019) and for which the ratio between FTHg and DOC was found to be 0.30 AE 0.19 ng mg −1 (compiled from 31 studies on 1973 samples) and the ratio between FMeHg and DOC was found to be 0.045 AE 0.06 ng mg −1 (compiled from 20 studies on 1068 samples). These relationships suggest similar binding capacities of DOC to THg and MeHg in watersheds across a large geographic gradient.…”
Section: Transport and Sources Of Mercury In Riverssupporting
confidence: 89%
“…Positive relationships between FTHg and FMeHg with DOC have been observed in numerous fluvial Hg studies (Balogh et al 2008;Brigham et al 2009;Schuster et al 2011;Tsui and Finlay 2011;Bravo et al 2018;Lavoie et al 2019) because DOM is presumed to be the dominant carrier of inorganic Hg and MeHg in surface water through complexation with thiol groups (Ravichandran 2004).…”
Section: Transport and Sources Of Mercury In Riversmentioning
confidence: 95%
“…Recent studies have found strong relationships between total DOM concentrations, and in particular, terrestrial DOM pools with THg concentrations (Bravo, Kothawala, et al, 2018; Lavoie et al, 2019), because Hg is bound to DOM and they are comobilized from land to water. Interestingly, when all sites were considered (including tributaries and groundwater that had higher values), we observed a slope of 0.28 ng/mg in the linear regression between THg and DOC, comparable to the average global slope identified in a recent meta‐analysis for freshwater (Lavoie et al, 2019). We also observed an association between concentrations of DOC, DOM components C2 and C4 (identified in our PARAFAC model as humic‐like DOM presumably of terrestrial origin) and THg, suggesting that colored, terrestrial DOC is a good proxy for the loading of Hg in the Romaine watershed.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these model results imply that environmental influences over the Hg cycle are more important determinants of terminal piscine [THg] than alterations to the food web structure in La Mauricie National Park lakes. Indeed, DOC plays a complex role in the bioavailability of Hg in freshwater ecosystems (Ravichandran 2004; Lavoie et al 2019). Several studies have reported positive relationships between aqueous [THg] and/or [MeHg] with [DOC] in freshwaters (Driscoll et al 1995; Scudder 2010; Braaten et al 2014; Lescord et al 2018; Lavoie et al 2019; Wu et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DOC plays a complex role in the bioavailability of Hg in freshwater ecosystems (Ravichandran 2004; Lavoie et al 2019). Several studies have reported positive relationships between aqueous [THg] and/or [MeHg] with [DOC] in freshwaters (Driscoll et al 1995; Scudder 2010; Braaten et al 2014; Lescord et al 2018; Lavoie et al 2019; Wu et al 2019). Dissolved organic matter and/or DOC can influence Hg levels of freshwaters by facilitating the export of inorganic Hg and MeHg from watersheds to waterbodies (Driscoll et al 1995; Hurley et al 1995).…”
Section: Discussionmentioning
confidence: 99%